Kepemimpinan Transformasional dan Kompetensi terhadap Peningkatan Motivasi serta Dampaknya pada Kinerja Perawat - Eka Puspita; Sonny Hersona GW; Hawignyo Hawignyo (Journal of Management and Bussines (JOMB), 2022)
The purpose of this study was to determine the description of transformational leadership, nurse competence, increasing nurse motivation, and nurse performance at Dewi Sri Hospital Karawang. This research method uses descriptive and verification with a quantitative approach. The data analysis technique used is (path analysis), with hypothesis testing t test and f test. The results of the study show, there is a strong and significant influence between leadership transformation on work motivation, there is a strong and significant influence between nurse competence on work motivation, there is a strong and significant influence between work motivation and nurse performance. There is a strong and significant influence simultaneously between transformational leadership and nurse competence on nurses' work motivation. Conclusion, transformational leadership has a dominant effect on nurses' work motivation. The competence of nurses gives a significant contribution to work motivation. This means that the better the nurse's competence, the work motivation will increase. The work motivation of nurses at Dewi Sri Hospital is largely determined by these two variables. Keywords: Transformational leadership, Nurse performance, Work competence, Work Motivation